Contribution of different types of terrestrial protected areas to carbon sequestration services in China: 1980–2020 - Tian, Jing; Feng, Chunting; Fu, Gang; Fan, Luqiong; Wang, Wei (Frontiers in Ecology and Evolution, 2023)
Exploring the contribution of protected areas to carbon sequestration services is meaningful to enhance the role of protected areas in climate change mitigation globally. However, less attention has been paid to the contribution of different types of protected areas to carbon sequestration services as well as their changes, which is not conducive to provide more effective solutions in the context of future climate change. Here we identified the status and changes of carbon sequestration in different types of terrestrial protected areas in China and calculated the amount of carbon sequestration in different ecosystems in terrestrial protected areas and in different climatic zones. Our results indicated that carbon sequestration of China’s terrestrial protected areas had shown a significant increasing trend over the past 40 years (1980-2020) (R2 = 0.862, P < 0.05). Among the different types of terrestrial protected areas in China, nature reserves had the greatest carbon sequestration, accounting for 64% to 66% of the carbon sequestration in China’s terrestrial protected areas from 1980 to 2020. Although the carbon sequestration per unit area of forest parks was the highest among all types of protected areas, the proportion of carbon sequestration of forest parks tended to decrease significantly over the past 40 years. Carbon sequestration of protected areas in the humid zone had been mainly contributed by forest ecosystems, while grassland and desert ecosystems in terrestrial protected areas in regions with low rainfall (e.g. semi-arid and arid) had made more contribution to carbon sequestration services. Our study showed that China’s terrestrial protected areas had played an important role in carbon sequestration over the past 40 years, but there are still some gaps compared to the global level, and the planning and establishment of protected areas need to be further strengthened in the future.